2019
DOI: 10.1021/acs.jpcc.9b07620
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Ordering of Ammonium Cations in NH4I, NH4Br, and NH4Cl

Abstract: Different types of magnetism arise mainly from how electrons move and interact with each other. In this work, we show how protons (H+) also exhibit magnetic behavior. We measured the magnetic susceptibility of the ammonium halides and identified pronounced increases at 232, 233, and 243 K for NH4I, NH4Br, and NH4Cl, respectively, all of which coincide with the geometric ordering of their ammonium cations. With extensive literature establishing the fact that the ammonium cations exhibit rotational motion even t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 51 publications
1
13
0
Order By: Relevance
“…In particular, reorienting ammonium cations NH 4 + carry a magnetic moment because the enclosed areas of the orbits of the positive and negative charges are different, so their respective magnetic moments do not cancel each other out (Figures 1a and 1b). The associated moment is only 0.0016 μ B ; 6 however, due to the shape and symmetry of the periodic potentials, the NH 4 + only exhibits C 2 and C 3 reorientations, so the directions of the moments are restricted to only point along 14 directions (along the diagonals and faces of a cube) which dramatically enhances intermolecular orbital interactions. From such, we concluded that it is the long-range ordering of the proton orbitals in the ammonium halides that triggers their geometric ordering and consequential structural phase transitions.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In particular, reorienting ammonium cations NH 4 + carry a magnetic moment because the enclosed areas of the orbits of the positive and negative charges are different, so their respective magnetic moments do not cancel each other out (Figures 1a and 1b). The associated moment is only 0.0016 μ B ; 6 however, due to the shape and symmetry of the periodic potentials, the NH 4 + only exhibits C 2 and C 3 reorientations, so the directions of the moments are restricted to only point along 14 directions (along the diagonals and faces of a cube) which dramatically enhances intermolecular orbital interactions. From such, we concluded that it is the long-range ordering of the proton orbitals in the ammonium halides that triggers their geometric ordering and consequential structural phase transitions.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Consequently, most hydrogen-bonded systems are diamagnetic, which in theory should have a magnetic susceptibility of χ e = μ 0 ·μ e · N / H (where μ 0 , μ e , N , and H are the permeability of free space, magnetic moment of the electron, number of atoms per unit volume and applied magnetic field, respectively) . Not only does this constant not hold true for most hydrogen-based materials, the susceptibility for many also varies with temperature. This can mean that either the motion of protons disrupts the diamagnetic response of the electrons or the protons have an orbital magnetic moment of their own. In either case, most models treat the protons as rigid and continue to overanalyze the behavior of the electrons which are all paired up so their effects cancel each other out.…”
mentioning
confidence: 99%
“…Although it is fair to dismiss the protons as static charges since their motions always bring them back to their original equilibrium positions, leaving the lattice essentially unchanged, during the process of traveling from one equilibrium point to another, a magnetic field is generated. Recently, we showed how the orbital motion of protons in reorienting NH 4 + tetrahedra at rates of 10 12 Hz generates a magnetic moment that is larger than the intrinsic spin of the proton . The magnitude of these orbital moments is nearly 3 orders of magnitude smaller than that of an electron; however, in the proton disordered state, the proton moments can only point along a discrete number of directions due to the 4-fold nature of the potentials confining each NH 4 + .…”
mentioning
confidence: 99%
See 2 more Smart Citations